(untitled) (Journal of Organizational Psychology, 2017)
With the advent of globalization and increased competition, there is a dire need to espouse a proactive approach on the part of the employer and work towards ensuring employee retention. Hence in the present study we proposed and empirically tested a research model which examined the factors affecting retention of employees. This multilevel model aimed at testing both organizational level factors— organizational commitment and managerial communication and individual/employee level factors— perceived organizational support, job satisfaction and job performance. Overall, using SEM, the research model demonstrated a good fit and provided evidence for a robust relationship between managerial communication and retention. Implications for organizations and future research are discussed.